Inactivation of Coronaviruses in food industry: The use of inorganic and organic disinfectants, ozone, and UV radiation - Quevedo-León, Roberto (2020)
Currently there is a worldwide pandemic due to Covid-19, which has caused a great impact on humanity in social, economic, psychological aspects and unfortunately on health. Due to the risk that food can also be a medium to cause virus diseases, the procedures in the food industry safety programs must be revised; and, to be more specific, to disinfect Covid-19. Some effective disinfectants that have been proved to inactivate the coronavirus are: chlorine dioxide, sodium hypochlorite, quaternary compound, ozone and UV-C (shortwave ultraviolet light). In this review, some treatments used to inactivate a virus, with an emphasis to the coronavirus family, and other influenza viruses, are reported. It has been concluded that the coronavirus could be inactivated using free chlorine solutions at 30 mg/L, sodium hypochlorite 0.25 %, or Chlorine Dioxide (99% purity) diluted at 1/2.5 relation. Also, alcohol is an effective disinfectant at concentrations of 62 to 71% of ethanol. With respect to the use of the quaternary compound, it can be used at concentrations of 0.10%. Ozone is another promising disinfectant to inactivate the coronavirus and Covid-19. Doses of ozone between 10 to 20 ppm for 10 to 15 minutes are recommended to inactivate the coronavirus with 3.5 log10 reductions. However, a warning should be reported to the use of high doses of exposure because it can be a risk to human health. UV-C can inactivate the coronavirus at a value of 67 J/m2 by 1 to 30 minutes of exposure.